Synthesis, Spectral Identification, Antibacterial Evaluationand Theoretical Study of Co, Fe, Rh and Pd Complexes for 2-benzoylthiobenzimidazol - Israa H. Ibraheem; Amaal S. Sadiq; Maha Al-Tameemi; Mahasin F. Alias (مجلة بغداد للعلوم)
A new novel series of metalcomplexes are prepared from reactions between 2-benzoylthio- benzimidazole (L) with metal salts of Co (II) , Fe(III) and Rh (III) , while Pd(II) complex was obtained by mixing ligandsof 2-benzoylthiobenzimidazole (L) as primary ligand and bipyridine (L/)as secondary ligand as well as palladium chloride as metal salt in an ethanoic medium. The geometry of these compounds were identified using C.H.N.microanalysis, Ultraviolet–visible, Fourier transforms infrared, magnetic susceptibility, molar conductivity and flame atomic absorption (A.A). From the dataobtained by these spectral analyses, the molecular structures for Rh and Fe complexes were proposed to be octahedral geometry. A square planar construction is proposed for Pd(II), while a Tetrahedral Geometry for Cobalt (II)complex. All of the complexes which were prepared displayedobviousconstancy and could be stored for months without showing any considerablealteration. Semi-empirical methods (ZINDO/1, ZINDO/S & PM3) were conducted to assess the heat of formation ∆H˚f, binding energy ∆Eb, and dipole moment for all compounds as theoretic study. The complexes expressnotable biological activities to pathogenic bacteria when inspected on certain bacteria. The synthesized compounds exhibited moderate toverygood antibacterial activity against bacterial strains, i.e., Escherichiacoli, Staphylococcus aureus & Pseudomonas aeruginosa.